Hubungan Kualitas Pelayanan dan Komunikasi Bidan Terhadap Tingkat Kepuasaan Ibu Hamil Pada Pelayanan Antenatal Care di Puskesmas Tanjungan Rambang Kota Prabumulih Tahun 2025 - Marita Eka Sari; Ratna Dewi; Sendy Pratiwi Ramadhani; Putu Lusita Nati Indriani (STIKes Budi Mulia Sriwijaya, 2025)
Antenatal care is a service provided by health workers to mothers during pregnancy. Maternal satisfaction can be defined as a feeling of pleasure and satisfaction felt by pregnant women towards the health services received during pregnancy. The purpose of this study was to determine the relationship between the quality of service and midwife communication with the level of satisfaction of pregnant women in antenatal care services simultaneously and partially at the Tanjung Rambang Community Health Center in 2025. Factors that influence maternal satisfaction include the quality of communication of health workers, the quality of health services, attitudes and behavior of health workers. The research method used an analytical survey with a cross-sectional approach. The study was conducted in April - August 2025 at the Tanjung Rambang Community Health Center. From preliminary survey data at the Tanjung Rambang Community Health Center, data were obtained on 123 pregnant women who underwent antenatal care in January - May. The sample of this study used the Accidental Sampling technique, namely by taking respondents who happened to be available at the time of the study, amounting to 56 respondents. The results of the showed that there was a significant relationship between the quality of service with the value (P-Value = 0.000), there was a significant relationship between midwife communication with the value (P-Value = 0.033), on the level of satisfaction of pregnant women in antenatal care services at the Tanjung Rambang Health Center in 2025. The conclusion is that there is a relationship between the quality of service and midwife communication with the level of satisfaction of pregnant women. It is hoped that the health center will conduct patient satisfaction surveys periodically as evaluation material for improving patient satisfaction services.